The Relationship between Awareness of the Impact of Fast Food, Sugar and Processed Food on Health with Food Intake - Md Kamaruddin, Nafisah @ Kamariah; Wan Nur Anis Meor Aznam,; Adnan, Nur Amirah; Armira Aini Asmi, (Multidisciplinary Applied Research and Innovation, 2021)
There are so many campaigns and advertisements on television on the danger of consuming too much fast food, sugar, and processed food. However, people still neglect and consume these foods in high amounts, especially the younger generation. Thus, the purpose of this study is to identify the relationship between the awareness of the youngster on the impact of fast food, sugar, and processed food on health with food intake. This study was conducted through Google form, which was distributed online, and the data are analyzed using Statistical Package for the Social Sciences (SPSS) in finding the correlation between awareness and their eating habit. A total of 167 students participated in answering the questionnaire with one section on demography and six sections comprising of thirty questions. It is found that there is a correlation between knowledge of fast food and attitude in consuming fast food, the correlation between knowledge on sugar and attitude in consuming sugar, and the correlation between knowledge of processed food and attitude in consuming process. Even though respondents realize the danger of consuming these foods, they still take in a high amount. This shows that they are aware of the danger but refuse to take care of their health.